Validation of the Quality of Life Scale (QLS) Malay Version among Patients with Schizophrenia - Othman, Zahiruddin; Ghazali, Malihah (Japan International Cultural Exchange Foundation, 2017)
Objectives: The Quality Of Life Scale (QLS) is an English version of semi-structured interview that assesses quality of life (QOL) among patients with schizophrenia. The aim of this study was to translate and validate the QLS into Malay version for more widespread use in clinical practice. Methods: This study was conducted on 30 schizophrenia patients attending Hospital Raja Perempuan Zainab II (HRPZ II) and Hospital Universiti Sains Malaysia (HUSM). The QLS was translated into Malay language using forward and backward translation method. The final Malay version of the QLS was tested for the content validity by two experienced psychiatrists. Its face validity was tested on 10 Malay patients with schizophrenia. The internal consistency analysis was performed by measuring Cronbach's alpha in all four domains of QLS Results: The Malay version QLS was found to have good content and face validity. It also displayed good internal consistency with Cronbach's alpha of between 0.87 and 0.93. Conclusion: The Malay version QLS is a good tool to be used in future research to assess quality of life of patients with schizophrenia.